2014
DOI: 10.1021/ie500739h
|View full text |Cite
|
Sign up to set email alerts
|

Data Reconciliation and Dynamic Modeling of a Sour Water Gas Shift Reactor

Abstract: Integrated gasification combined cycle (IGCC) plants with CO 2 capture have strong potential in the future carbon-constrained world. In these plants, the CO 2 and COS content of the syngas at the inlet of the acid gas removal process should be within certain limits in order to satisfy the environmental limits on sulfur and CO 2 emissions. To satisfy these constraints, the syngas from the gasification process is passed through water gas shift reactor(s). A premium is placed on sulfurtolerant catalysts since the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The Ergun equation is used to calculate the pressure drop inside the reactor where M gas is the molecular weight of the gas (kg/kmol); and P is the reactor pressure (bar). The boundary condition is as follows: P ( z = 0) = P inlet .…”
Section: Fixed Bed Reactor Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ergun equation is used to calculate the pressure drop inside the reactor where M gas is the molecular weight of the gas (kg/kmol); and P is the reactor pressure (bar). The boundary condition is as follows: P ( z = 0) = P inlet .…”
Section: Fixed Bed Reactor Model Developmentmentioning
confidence: 99%
“…The mass transfer coefficient ( k gas, i ) and the bulk gas heat transfer coefficient ( h gc ) are calculated using the correlations given by Mobed et al and Barton and Adams II . Like before, the physical properties of the gas used in these equations are calculated using SRK EOS in ACM.…”
Section: Fixed Bed Reactor Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the parameters for the WGS reaction need to be obtained by analyzing the available experimental data (Berispek et al, 1975). It was found that measurement errors were present in the data collected in experimental studies; a data reconciliation procedure is performed to obtain consistent data (Mobed et al, 2014).…”
Section: Reaction Kineticsmentioning
confidence: 99%
“…Under these circumstances, solving a DDR problem becomes necessary (Montañés et al, 2017). This step becomes critical for validation of dynamic models and estimation of model parameters (Mobed et al, 2014).…”
Section: Dynamic Model Developmentmentioning
confidence: 99%